The pre-urban and anthropogenic geomorphological cartography of the Pinheiros River plain, São Paulo (SP) - Luz, Rodolfo Alves da (2024)
This paper presents a comparative analysis based on maps of the anthropogenic and pre-urban geomorphology of the Pinheiros River fluvial plain in the São Paulo city. The pre-urban and anthropogenic conditions of the river system were mapped through a historical approach and geomorphological cartography, which allows for a retrospective and evolutionary analysis of the system throughout urbanization. The cartographic analysis was carried out based on the production of geomorphological maps at a scale of 1:25,000, elaborated mainly through stereoscopic restitution of aerial photographs from the 1930s and field surveys, with the aid of ancient and current cartographic bases. The maps revealed both the geological and geomorphological evolution and the anthropogenic modifications, as well as the magnitude and consequences of urbanization in the system. The urban geomorphological changes were classified as instantaneous (100 to 102 years), comparable only to extreme and high-magnitude natural events or millennial events (103 to 104 years). Furthermore, the urbanization of the Pinheiros River fluvial plain has resulted in a hydromorphological system with virtually no original floodplain remnants that could be utilized to control peak floods. The Pinheiros River case study demonstrates how urban interventions based solely on the structural engineering often fail to consider the complex response that geomorphological processes can exhibit when thresholds are disrupted.